2022
DOI: 10.1016/j.jdmm.2021.100676
|View full text |Cite
|
Sign up to set email alerts
|

Marketing messages for post-pandemic destination recovery- A Delphi study

Abstract: What is the best way to communicate with American outbound visitors as the travel recommences after the COVID-19 pandemic? This timely study aimed to find answers to this question faced by many destinations. To this end, ideas were sought from industry and academic experts on what message features may positively influence American visitors international travel intentions following the COVID-19 pandemic. Three rounds of conventional Delphi research delivered fifteen message features, eight of which attained pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 65 publications
0
20
0
4
Order By: Relevance
“…Recent studies in management and marketing research have focused on the identification of new and effective strategies for destination marketing and image creation in the COVID crisis scenario, aimed at prospective growth in post-pandemic tourism [11,[46][47][48]81]. Glyptou [46] emphasized that positive image creation of a destination during times of a prolonged crisis, such as COVID-19, acts as a predictor of tourist intentions for visiting destinations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies in management and marketing research have focused on the identification of new and effective strategies for destination marketing and image creation in the COVID crisis scenario, aimed at prospective growth in post-pandemic tourism [11,[46][47][48]81]. Glyptou [46] emphasized that positive image creation of a destination during times of a prolonged crisis, such as COVID-19, acts as a predictor of tourist intentions for visiting destinations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the physical factors of the destinations were found to be more influential. Similarly, Singh et al [48] identified marketing methods that can help destinations and tourism businesses to sustain and stand out during a crisis, such as COVID-19. The authors suggested COVID-related marketing attributes for opening destinations after the pandemic, vaccinated staff, open and outdoor spaces, and other information to increase traveler's engagement and confidence that would consequently affect their visit intentions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations